Heitor Villa-Lobos’s Magdalena: classical music, the Broadway stage and the challenges of reimagining - Hess, Carol A. (Comparative Cultural Studies: European and Latin American Perspectives, 2023)
This essay explores Magdalena, the sole foray into the Broadway musical by the celebrated Brazilian composer Heitor Villa-Lobos, which premiered in 1948. Until recently, “serious” musicology treated the musical only rarely. Nowadays, however, many scholars have analyzed the musical—considered by many the “quintessentially American” genre—from aesthetic, social, cultural, and political perspectives. Musicological study of Villa-Lobos reflects this bias: previously, scholars concentrated on his symphonies, his piano music, his chamber works, and his operas, largely overlooking Magdalena. In this project, Magdalena is the main focus. I evaluate Villa-Lobos’s status in the United States, relating the reception of his works to prevailing images of Latin American music. I propose that Magdalena, known in theater circles as the “Latin American musical,” constitutes a chapter, albeit a brief one, in the discourse of “tropicalization,” a term coined by Frances R. Aparicio and Susana Chávez-Silverman to refer to the tendency on the part of the mass audience in the U.S. to reduce Latin America to a unitary fantasy, a phenomenon that aptly meshes with some of the values of the classic Broadway musical. Finally, since many classic musicals are now being reshaped in accordance with current sensibilities on race, gender, class, and identity, I offer possible reimaginings of Magdalena.